2006
DOI: 10.1088/0268-1242/21/7/004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a-GaAs/a-Si double buffer layers on GaAs-on-Si as determined by transmission electron microscopy

Abstract: A high-quality GaAs epilayer was successfully grown on a Si substrate using a-GaAs/a-Si double buffers, which were crystallized by thermal cyclic annealing. Double crystal x-ray diffraction measurements showed that the full width at half maximum of the rocking curve for the GaAs epilayer was only 102 arcs. The effect of a-GaAs/a-Si double buffers was examined in detail by transmission electron microscopy. Transmission electron microscopy characterizations revealed obvious bending behaviour of dislocations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…8(a), the pits were counted according to the sizes and the results were listed in the right top of the same figure. As was reported elsewhere, there were much more dislocations and therefore more complicated dislocation behaviors in the a-GaAs/a-Si buffered GaAs-on-Si specimens, such as the bending or interactions of dislocations observed by transmission electron microscopy (TEM) [22]. As a result, it is possibly to cause a variation in the dislocation numbers along the epilayer thickness.…”
Section: Article In Pressmentioning
confidence: 74%
“…8(a), the pits were counted according to the sizes and the results were listed in the right top of the same figure. As was reported elsewhere, there were much more dislocations and therefore more complicated dislocation behaviors in the a-GaAs/a-Si buffered GaAs-on-Si specimens, such as the bending or interactions of dislocations observed by transmission electron microscopy (TEM) [22]. As a result, it is possibly to cause a variation in the dislocation numbers along the epilayer thickness.…”
Section: Article In Pressmentioning
confidence: 74%
“…1,2 In addition, the epitaxial silicon-germanium (epi-SiGe) film can serve as a template for high-performance multi-junction solar cells due to a tunable energy band gap that is a function of the Ge fraction. [3][4][5] Conventionally, the epi-SiGe film can be grown using chemical vapor deposition (CVD), 6 or molecular beam epitaxy (MBE); 7 however, these techniques usually require strict conditions of high vacuum, high temperature, and use of toxic precursors. It was reported that the epi-SiGe film can be fabricated using an Al solid phase epitaxial (AI-SPE) process from a-Ge/Al layers on a Si substrate after annealing at 300 °C.…”
mentioning
confidence: 99%
“…Thus no lattice mismatch strain is present at the GaAs/Si interface, and dislocations are unnecessary in the GaAs layer, although dislocations and planar defects can occur in the a-Si layer. [24,25] By introduction of a thin a-Si layer on the surface of Si wafers, the dislocation density in GaAs/Si epilayers was reduced effectively. [24−27] Hao et al obtained 2.2-µm GaAs/Si epilayers through use of a 15-Å a-Si layer as buffer layer, and GaAs/AlGaAs quantum well lasers were achieved on silicon.…”
mentioning
confidence: 99%
“…[24−27] Hao et al obtained 2.2-µm GaAs/Si epilayers through use of a 15-Å a-Si layer as buffer layer, and GaAs/AlGaAs quantum well lasers were achieved on silicon. [26,27] Insertion of a 20-Å a-Si layer before the two-step growth process, Uen et al [24,25] achieved 4-µm GaAs/Si epilayers with an etch-pit density close to 1 × 10 6 cm −2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation